Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. Issue 3 (26th November 2016) - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T.; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Gibbs, Richard; Bonafe, Luisa; Campos‐Xavier, Ana Belinda; Unger, Sheila; et al.
Abstract : Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture‐like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1 . These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.